Anatomo-Politics and Biopolitics in Paradise Film (2023): A Study of Biopower by Michel Foucault - Amirudin Amirudin; Tutik Ratna Ningtyas; Bambang Irawan; Christy Tisnawijaya (Doctoral Program of Social Science Pasundan University, 2026)
Paradise film (2023) by Boris Kunz presents a dystopian premise of longevity in which “chrono-transfer” enables people to trade for their life years. Rich people can buy youth while poor people sell their life years as a means of survival. This article examines the film using Foucault’s biopower framework, focusing on how chrono-transfer technology represents the privatization of life and body control in liberal capitalism. Through qualitative analysis of essential scenes and dialogs such as Elena’s contract, Elena’s body transformation, and bio-hierarchy dialogs, this article explains its two main findings. The first finding is that anatomo-politics operates within Elena’s body through contract mechanisms, instantaneous body transformation, and self-surveillance. The second finding is that the chrono-transfer system produces population biopolitics in which longevity is unequally distributed, reflecting “state racism”.